(untitled) (International Journal of Food and Nutritional Sciences, 2022)
There are 57 insurance companies in India’s insurance market. 33 insurers are not life insurers, while 24 are in the life insurance industry. Life Insurance Corporation (LIC) is the only company in the public sector that provides life insurance. In the non-life insurance business, there are six public sector insurers. In addition to these, General Insurance Corporation of India is the only national re-insurer (GIC Re). Agents (individual and corporate), brokers, surveyors, and third-party administrators handling health insurance claims are other market participants in India. Nature is unpredictable and uncertain. The same is true for a person’s life, which in this unstable world is full with hazards and uncertainties. Any type of misfortune can result in anything from mild to severe injuries to even death. Diseases do not ever come knocking at our bodies’ doors. Insurance is the ideal way to deal with difficult times in our lives and the lives of our loved ones when we depart for our heavenly abode. Money has never been able to buy life or heal diseases, and it never will. The present study is an attempt to summarize the current state of the general insurance, which includes health insurance, industry in India. Due to the introduction of private health care funders, rising health consciousness among all societal segments, rising household income, price and service competition among health insurers and a lack of bureaucracy, the health insurance sector in India has experienced tremendous growth since liberalization in employees with health insurance.